Desarrollo del lenguaje en la lecto-escritura en estudiantes de la Escuela de Educación Básica Albert Einstein, período 2024 – 2025 - Ramírez Cabrera, María del Cisne (2024)
The development of language in reading and writing constitutes a fundamental area in education, as it is a multidimensional process that encompasses the acquisition and application of language skills, which are essential for effective communication. This process involves the comprehension and elaboration of written texts, as well as the ability to interpret and generate ideas in spoken and written form. The objective of this paper was to analyse the reading-writing language development in some students; we selected a sample population from the Albert Einstein Basic Education School, period 2024-2025, it was a total of 1 teacher and 18 students. This research had a qualitative, descriptive approach, with a non-experimental design and a cross-sectional axis, using the hermeneutical, inductive, analytic-synthetic and scientific method; we used the technique of interview and observation. The results evidenced significant variations in language development among students, some of them showing remarkable abilities in verbal fluency, text comprehension and grammar use, while others presented deficiencies in pronunciation, sentence formation and fluent reading. In addition, the results revealed that several students have difficulties to express themselves clearly and follow an adequate grammatical structure, which negatively affects their academic performance and their motivation to participate in reading-writing activities. Consequently, it is concluded that a substantial group of students have pronunciation, sentence formation, clear communication and fluent reading difficulties; the strategies implemented by the teacher, although adequate, need a more individualized and adaptive approach to address all those various needs; therefore, there was a need to design an intervention proposal called “Methodological strategies to strengthen language development and literacy” to provide teachers and students with effective tools for strengthen and improve language skills and literacy.